Role of Dietary Zinc in Heat Stressed Dairy Animals: A Review - Patel, Brijesh; Jain, Varsha; Ajitha Kumar, H. M.; Lokesha, E.; Purwar, Vaibhav; Prabhakar, Arun; Kumar, Nishant (International Journal of Livestock Research, 2018)
High ambient temperatures compromise performance and productivity by reducing feed intake and decreasing nutrient utilization, growth rate, feed efficiency and milk production which lead to economic losses in dairy farming. Environmental stress also leads to oxidative stress associated with a reduced antioxidant status in the animals in vivo, as reflected by increased oxidative damage and lowered plasma concentrations of antioxidant vitamins (e.g., vitamins E, A, and C) and minerals (e.g., Zn). Zinc has an important role in numerous biological processes in avian and mammalian species. For instance, Zn is an essential component of many enzymes, and it has both structural and catalytic functions in metalloenzymes. Furthermore, dietary Zn is required for normal immune function as well as proper skeletal development and maintenance. One of the most important functions of Zn is related to its antioxidant role and its participation in the antioxidant defense system. This work compiles past and present information about the role of Zn in heat-stressed dairy animal’s health.